TOP-DOWN COLLABORATIVE GOVERNANCE : DINAMIKA KOLABORASI MULTI AKTOR DALAM PENGELOLAAN PROGRAM KAMPUNG IKLIM DI KELURAHAN TUGUREJO KOTA SEMARANG - Rizka Utami (Journal of Politic and Government Studies, 2026)
Climate change is a global phenomenon whose impacts are particularly felt in coastal areas, including Tugurejo Village. The main challenge in climate change adaptation and mitigation efforts lies in the complexity of climate change issues, which cannot be addressed by a single actor but require cross-sectoral synergy. This study aims to analyze collaborative governance practices in the management of the Climate Village program in Tugurejo Village using the Ansell and Gash model. The focus of this study is to examine the roles of stakeholders and the dynamics of collaboration among government actors, academics, the private sector, and the community. The research method employed is descriptive qualitative. Data were collected through in-depth interviews and document analysis. Data analysis was conducted based on the collaborative governance theory developed by Ansell and Gash. The research findings indicate that the Proklim program in Tugurejo Village tends to be top-down in nature. A significant power imbalance was identified, with the Semarang City Environmental Agency dominating as both the initiator and the entity determining the direction of the work. Furthermore, the institutional design, which remains informal, and the reliance on a “local hero” figure make the program’s sustainability vulnerable to external changes. The conclusion of this study is that collaborative practices in Tugurejo are more of an instructive coordination than an equal partnership, thus requiring the strengthening of a more formal institutional design and the redistribution of power and knowledge. Therefore, it is recommended that cooperation be formalized in writing and that leadership regeneration at the grassroots level be strengthened to ensure the program’s autonomy in the future.